A comparative study of avian pes morphotypes, and the functional implications of Australian raptor pedal flexibility. (2nd January 2019) - Tsang, Leah R.; McDonald, Paul G.
ABSTRACT: The hind limbs and feet of birds are the primary structures used for important tasks such as perching (e.g. Passeriformes), food procurement (e.g. diurnal and nocturnal raptors) and object manipulation (e.g. Psittaciformes). Birds of prey or 'raptors' in particular rely heavily on their feet to hunt and capture prey, with their toes equipped with sharply curved talons to facilitate prey restraint, prevent escape, and fatally wound prey. We hypothesise that raptors, being more reliant on their toes and digits for prey capture, will have greater pedal flexibility when compared with non-raptorial groups. We analysed pedal flexibility across four avian pedal morphotypes (anisodactyl, zygodactyl, facultative zygodactyl, and raptorial) representing both raptor and non-raptor groups by measuring the maximum angle of divarication between digits Dii, Diii, and Div . The anisodactyl morphotype (Corvidae) had the lowest measurements (min. 29°; max. 88°), and the zygodactyl morphotype (Cacatuidae) had the widest minimum and maximum digit angle divarication measurements (min. 115°; max. 166°). The facultative zygodactyl morphotype (Pandionidae, Strigidae, Tytonidae) had higher pedal flexibility than the anisodactyl morphotype. Within the anisodactyl morphotype, we compared raptor and non-raptor groups and found that the raptorial morphotype had the widest range of motion (76°) when compared with the other morphotypes. Further, within the raptorial morphotype group, there was a clear separation in pedal flexibility particularly between dietary specialists and generalists. The increased pedal flexibility of raptors could be shaped by physical adaptation to predatory behaviours and dietary choices.